The poor in the Epistle of James and the Gospel of Thomas - Hartin, Patrick (Hervormde teologiese studies, 1997)
This study explores similarities in the thought world of the Epistle of James and the Gospel of Thomas. Particular attention is devoted to the role that the 'poor' and 'poverty' play in both documents. For the Epistle of James it is 'the poor in the world that God has chosen to be rich in faith and heirs of the kingdom' (Ja 2:5). In a similar vein, in the Gospel of Thomas the kingdom is promised to those who have embraced the poverty of a radical life-style: 'Blessed are the poor, for yours is the kingdom of heaven' (GTh 54). This outlook betrays a basic ethos adopted toward the world. In both the Epistle of James and the Gospel of Thomas the relationship to the world ultimately determines one's relationship to the kingdom or to God. For the Epistle of James the very definition of religion demands that one keep 'oneself unstained from the world' (Ja 1 :27) and that 'friendship with the world' is enmity with God (Ja 4:4). For the Gospel of Thomas the rejection of the world involves a radical ethos that embraces an intinerant life ('Be passersby' [GTh 42J), which includes a rejection of wealth (GTh 63).'If you do not abstain from the world, you will not find the kingdom' (GTh 27). It is argued that the Gospel of Thomas and the Epistle of James reflect traditional sayings that endorse a similar ethos of radical discipleship.